2019
DOI: 10.1080/09687637.2019.1585759
|View full text |Cite
|
Sign up to set email alerts
|

Not without my mobile phone: alcohol binge drinking, gender violence and technology in the Spanish culture of intoxication

Abstract: The practice of binge drinking has in recent decades consolidated what is known as the 'culture of intoxication' among the young people of Spain. This has coincided with the increase in the use of mobile-phone technology and of social networks within the night-time economy. Our main aim is to explore these new, potentially risky uses and violent behaviours, through an analysis of the discourses of the young people involved. This is a qualitative study with in-depth interviews (n ¼ 24) of young people between t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 68 publications
2
11
0
3
Order By: Relevance
“…Previous research linked changes in gender roles and the consumption of certain substances; in the case of alcohol, there may be a direct relationship between these social changes in young people and alcohol consumption [21,[53][54][55]. Nevertheless, evidence from previous research reported greater polyconsumption in young men than in women [56].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous research linked changes in gender roles and the consumption of certain substances; in the case of alcohol, there may be a direct relationship between these social changes in young people and alcohol consumption [21,[53][54][55]. Nevertheless, evidence from previous research reported greater polyconsumption in young men than in women [56].…”
Section: Discussionmentioning
confidence: 99%
“…Males are more explicit in their responses because they understand that they can freely exercise activities related to nightlife, such as enjoying going out, partying, and alcohol and drug use, without these activities damaging their reputation or undermining their masculinity. The opposite happens with girls, who tend to take the stance and declare in their statements that "they are good girls", who repress their desire to drink alcohol and get drunk at parties, so as not to damage their "feminine" image, which is why they also follow rules of legal consumption [21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Este uso de las TIC, que tiene también un sesgo de género, afecta de distinta forma a chicos que a chicas. Para ellos ser grabados en estado ebrio o poses promiscuas no afecta a su reputación, en todo caso, suelen considerarlo divertido y un indicador de su papel protagonista en la fiesta; para las chicas, si esto ocurre, la imagen que proyectarían dentro del grupo en las mismas circunstancias sería negativa y peyorativa (Megías Quirós et al, 2005;Rodríguez Santero et al, 2017;Romo Avilés et al, 2019).…”
Section: Sesgo De Género En La Imagen Social Proyectadaunclassified
“…Estas imágenes sitúan a las chicas fuera del modelo normativo tradicional sobre la feminidad, que sigue exigiéndoles ser buenas, recatadas, decentes, pasivas. Actuar fuera de dicho modelo puede acarrear consecuencias como que sean objeto de insultos, vejaciones y hasta acoso sexual de diversos tipos (Romo Avilés et al, 2019). Esta constatación de las diferencias entre chicos y chicas viene a reafirmar la construcción cultural de la desigualdad en un marco sesgado por las relaciones normativas patriarcales de género en las que la igualdad no es más que un espejismo (Valcárcel, 2008;García-Carpintero, 2018).…”
Section: Introducción Estado De La Cuestión Y Objetivosunclassified